Peran Penyuluh Agama dalam Meningkatkan Religiusitas Masyarakat - Andhang Setyatmoko; Dian Tias Aorta (ANWARUL, 2026)
Community religiosity is an important aspect of social life because it reflects the level of understanding, internalization, and practice of religious teachings. In this context, religious counselors have a strategic role in improving community religiosity through various religious guidance activities. This study aimed to analyze the role of religious counselors in improving community religiosity in Sobo Village, Pacitan Regency. This study used a qualitative approach with a descriptive research design. Data were collected through observation, interviews, and documentation involving 10 participants consisting of religious counselors, community leaders, and residents. The results showed that religious counselors played a role in improving community religiosity through worship guidance, enhancement of religious understanding, and strengthening of socio-religious activities. Nevertheless, the level of community religiosity showed variations influenced by internal and external factors. These findings confirm that religious counselors have an important function as facilitators of religious guidance as well as agents of social change in the religious life of the community. The implications of this study indicate the need to strengthen the role of religious counselors in designing more contextual, participatory, and sustainable guidance activities to improve community religiosity.